UStore: A Low Cost Cold and Archival Data Storage System for Data Centers - Zhang, Quanlu; Li, Fengqian; Dai, Yafei; Zhang, Lintao (35th IEEE International Conference on Distributed Computing Systems (ICDCS), 2015)
Recent trend in cloud computing demands vast and ever increasing storage capacity for data centers. For many cloud service providers, much of the storage capacity demand is driven by cold and archival data, such as user uploaded contents, system logs, and backups. In this paper, we describe UStore, a hard disk based storage system designed for such workloads. We make the assumption that most data centers are already populated with computer servers and networking gears, and propose a solution to attach additional disks to these servers reliably at extremely low cost. The main component of UStore is a novel fat tree interconnect fabric to connect hard disks to existing servers and network infrastructure. To reduce cost, UStore leverages the mature commodity USB 3.0 technology to build the fabric, which has extremely low amortized cost per disk while still providing sufficient throughput to satisfy cold and archival workload. The software of the UStore system abstracts the system’s physical topology and provides a consistent view of the storage capacity to the upper layer services such as distributed file systems or backup services. In a sense, UStore can be regarded as external USB hard disks designed for data centers.